Faktor-faktor yang Mempengaruhi Produktivitas Kinerja Karyawan di PT Sari Aditya Loka-1 Menggunakan Regresi Linier Berganda - Riadil Jannah; Sherli Yurinanda (Pusat Riset dan Inovasi Nasional, 2025)
The key measure of employee performance productivity is determined by several factors, such as appropriate age, employee attendance rate (infrequent illness or leave), and the number of non-effective working days. To determine the extent to which these factors influence employee productivity, multiple linear regression analysis is used. The results of the analysis show that employee age has a significant influence on productivity, while non-effective working days and the frequency of employee illness or leave have little impact.